(untitled) (Energy and Automation, 2025)
Mykola Mykolayovych Zablodskyi is a well-known scientist in the field of electromechanics, Doctor of Technical Sciences, Professor, Honored Worker of Education of Ukraine. He was born on March 11, 1950 in the city of Pervomaysk, Luhansk region.